Developing a Policy Support System Model for Enhancing Rationality in Water Resource Management Using Structural Equation Modeling - Beheshti Rouy, Seyed Abdolhamid; Pourezzat, Ali Asghar; Nargesian, Abbas; Naghshineh, Nader; Movahedkhah, Zeinab (Management Strategies and Engineering Sciences, 2024)
The policy support system for enhancing rationality in water resource management is an analytical and decision-support tool that, using comprehensive physical, social, economic, and environmental data, assists managers and policymakers in making effective decisions based on facts and accurate information. The primary objective of this research is to design a policy support system to promote rationality in water resource management. A quantitative approach utilizing Structural Equation Modeling (SEM) was employed to design this system, with AMOS software used for analysis. Data collection was carried out using a questionnaire, whose validity was confirmed through construct validity and reliability measured by Cronbach's alpha coefficient at 0.87. The statistical population of this research consisted of managers and experts in the field of water management in Iran. The sample size was determined to be 256 individuals using the Morgan table. The quantitative data analysis led to the identification of 19 key components structured within the proposed model. These components include data collection and analysis, the use of geographic information systems, modeling and simulation, stakeholder analysis, decision support systems (DSS), legal and policy frameworks, performance evaluation and monitoring, training and capacity building, ensuring public participation and transparency, technology transfer and utilization, attention to climate change, inter-organizational alignment, continuous risk assessment and management, and integration with sustainable development, which can be employed in implementing the policy support system for enhancing rationality in water management.